Secukinumab sustains good efficacy and favourable safety in moderate‐to‐severe psoriasis after up to 3 years of treatment: results from a double‐blind extension study. (4th September 2017) - Bissonnette, R.; Luger, T.; Thaçi, D.; Toth, D.; Messina, I.; You, R.; Guana, A.; Fox, T.; Papavassilis, C.; Gilloteau, I.; Mrowietz, U.
Summary: Background: Secukinumab has demonstrated significant efficacy with a good safety profile through 1 year in plaque psoriasis. Given the chronic nature of this disease, long‐term follow‐up is needed to evaluate psoriasis therapies fully. Objectives: To determine the long‐term (3‐year) efficacy and safety of secukinumab in moderate‐to‐severe psoriasis. Methods: Patients completing 52 weeks of secukinumab treatment in the SCULPTURE core study entered an extension in which they continued the same double‐blind regimens. Dosing regimens included a fixed‐interval schedule (FI; every 4 weeks) and retreatment as needed (RAN), in which patients were withdrawn from secukinumab and received placebo until the start of relapse, at which time secukinumab every 4 weeks was reinitiated. The study was registered with number NCT01640951. Results: In total 168 patients receiving secukinumab 300 mg FI and 172 receiving secukinumab 300 mg RAN entered the extension. Secukinumab 300 mg FI sustained high efficacy: at the end of year 3, the proportion of responders achieving ≥ 90% improvement in Psoriasis Area and Severity Index (PASI 90) was 63·8%, and of PASI 100 responders it was 42·6%. The mean absolute PASI remained low (2–4) from week 52 to week 152 with 300 mg FI, with approximately two‐thirds of patients reporting no impact of skin disease on their lives (Dermatology Life Quality Index of 0 or 1). Improvements in overall and subscale scores on all quality‐of‐life instruments were well sustained. As in the core study, FI dosing was consistently more efficacious than RAN. No new safety signals were identified to year 3. Conclusions: Secukinumab 300 mg FI sustained high responses and improved quality of life with no new safety concerns through 3 years. Abstract : What's already known about this topic? Secukinumab, a fully human inhibitor of the inflammatory cytokine interleukin (IL)‐17A, has demonstrated efficacy with a good safety profile in moderate‐to‐severe plaque psoriasis through 1 year of treatment. Biological therapies for psoriasis have previously been associated with a fall‐off in efficacy over time; accordingly, extended follow‐up is required for adequate evaluation of novel therapeutic strategies like IL‐17A inhibition. What does this study add? Follow‐up data to 3 years confirm that the high responses initially achieved with secukinumab are sustained over time. A large proportion (63·8%) of patients treated with fixed‐interval secukinumab had ≥ 90% improvement in Psoriasis Area and Severity Index at year 3, with approximately two‐thirds reporting no impact of skin disease on quality of life. Patient‐perceived impairment of overall health status remained consistently low. No new or unexpected safety concerns emerged. Respond to this article